2013
DOI: 10.1364/oe.21.025159
|View full text |Cite
|
Sign up to set email alerts
|

A novel planar metamaterial design for electromagnetically induced transparency and slow light

Abstract: A novel planar plasmonic metamaterial for electromagnetically induced transparency and slow light characteristic is presented in this paper, which consists of nanoring and nanorod compound structures. Two bright modes in the metamaterial are induced by the electric dipole resonance inside nanoring and nanorod, respectively. The coupling between two bright modes introduces transparency window and large group index. By adjusting the geometric parameters of metamaterial structure, the transmittance of EIT window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(66 citation statements)
references
References 28 publications
0
66
0
Order By: Relevance
“…First, the gold nanoprism has stronger localization due to its sharper corner compared to a cuboid; 10,11 second, the variety of modes existing in the gold nanoprism makes coupling between the two nanoprisms much easier; 32 third, if the plasmonic microstructure is compared with the ''optical microcavity'', it is easy to see that the quality factor value (Q / 1/Dv) increases with the decrease of the linewidth of the transparency window brought about by the increased gap distance, as shown in Figure 3b, i.e., the photon lifetime increase corresponds to the strengthened slow-light effect. 33,34 We also investigated the dependence of the MIT lineshapes on the structural parameters, including the period of the dimers, the lateral length of the nanoprisms, the thickness of the gold nanoprisms, and different incident polarizations (detailed in the Supplementary Information). It was found that the MIT lineshape has an obvious red-shift with the increase of the period, whereas the lateral length and the gold thickness have little influence on the MIT.…”
Section: Resultsmentioning
confidence: 99%
“…First, the gold nanoprism has stronger localization due to its sharper corner compared to a cuboid; 10,11 second, the variety of modes existing in the gold nanoprism makes coupling between the two nanoprisms much easier; 32 third, if the plasmonic microstructure is compared with the ''optical microcavity'', it is easy to see that the quality factor value (Q / 1/Dv) increases with the decrease of the linewidth of the transparency window brought about by the increased gap distance, as shown in Figure 3b, i.e., the photon lifetime increase corresponds to the strengthened slow-light effect. 33,34 We also investigated the dependence of the MIT lineshapes on the structural parameters, including the period of the dimers, the lateral length of the nanoprisms, the thickness of the gold nanoprisms, and different incident polarizations (detailed in the Supplementary Information). It was found that the MIT lineshape has an obvious red-shift with the increase of the period, whereas the lateral length and the gold thickness have little influence on the MIT.…”
Section: Resultsmentioning
confidence: 99%
“…Slow-and fast-light effects are an important index, and it can be described by the group index n g [30] n…”
Section: The Transmission Characteristics With Varying Geometric Paramentioning
confidence: 99%
“…Plasmonic nanostructures are of considerable current interest because of their unusual electromagnetic and optical characteristics and the prominent applications in surface enhanced Raman scattering (SERS) [1], biological and chemical sensing [2], perfect light absorption [3], optical antennas and switching [4], slow-light devices [5], and imaging and cloaking. [6,7] The unique ability of plasmon to focus incident light into subwavelength regions near metal nanostructure surfaces can lead to very large local field concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that, both of the two resonances reveal a distinct plasmon shift with respect to a small fluctuation in the refractive index of the surrounding medium, and calculated average refractive index sensitivities are 900 nm/RIU and 493 nm/RIU, and corresponding figure of merits of two modes are 16 and 32 in vacuum, respectively. The sensing performance can be improved by changing the geometric parameters of planar metamaterial due to the plasmon modes coupling effect, which offer an excellent potential for optical nanosensing applications.& Elsevier B.V. All rights reserved.Plasmonic nanostructures are of considerable current interest because of their unusual electromagnetic and optical characteristics and the prominent applications in surface enhanced Raman scattering (SERS) [1], biological and chemical sensing [2], perfect light absorption [3], optical antennas and switching [4], slow-light devices [5], and imaging and cloaking. [6,7] The unique ability of plasmon to focus incident light into subwavelength regions near metal nanostructure surfaces can lead to very large local field concentration.…”
mentioning
confidence: 99%